Pendidikan Literasi Informasi di Perguruan Tinggi: Perspektif Refleksi dan Pendekatan Praktis Pelatihan Karya Tulis Ilmiah Mahasiswa - Donatus Dole (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2022)
Literacy education is important for students, from kindergarten to college. Even when a person has completed formal education and continues to work, knowledge about matters related to the field of work and its scope still needs to be deepened. This is what is meant by literacy education broadly. In a narrow sense, literacy means the ability to read, write and speak, both at the level of knowledge and up to the level of expertise. Thus, the scope of information literacy covers aspects of human life, on how to get information, how to use tools, and how to process what is found and known in a written work or real work.